2022
DOI: 10.1111/jfbc.14196
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of Angelica sinensis (Oliv.) Diels and Rehmannia glutinosa (Gaertn.) DC . on antioxidant activity and protective ability against cell injury

Abstract: Oxidative stress‐induced dysfunction of nerve cells has been implicated as a crucial cause of cell death in neurodegenerative diseases. In Asian countries, herbs, such as Angelica sinensis (Oliv.) Diels (DG) and Rehmannia glutinosa (Gaertn.) DC. (SDH), have long be considered to have antiaging abilities. The herbs act as neuro protectants that rescue nerve cells from oxidative stress damage and apoptosis. Thus, developing herbal formulas can potentially lead to new treatments for neurodegenerative diseases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…YCSND contained polysaccharides (408.55 ± 15.04 mg Glu/g), flavonoids (92.70 ± 3.37 mg RE/g), and polyphenols (39.76 ± 0.83 mg GAE/g) ( Supplementary Table S3 ). Additionally, YCSND showed excellent antioxidant activity against several free radicals, including DPPH, ABTS, O 2− and ·OH ( Supplementary Table S3 ), which was partly attributed to its polysaccharide, flavonoid, and polyphenol contents ( Zhang Q. et al, 2022 ; Ziyatdinova and Kalmykova, 2023 ). Moreover, UHPLC-QE-MS identified 89 metabolites, including 20 flavonoids, 18 terpenoids, 14 phenols, 11 phenylpropanoids, 11 alkaloids, three chalcones, and four coumarin derivatives ( Supplementary Table S4 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…YCSND contained polysaccharides (408.55 ± 15.04 mg Glu/g), flavonoids (92.70 ± 3.37 mg RE/g), and polyphenols (39.76 ± 0.83 mg GAE/g) ( Supplementary Table S3 ). Additionally, YCSND showed excellent antioxidant activity against several free radicals, including DPPH, ABTS, O 2− and ·OH ( Supplementary Table S3 ), which was partly attributed to its polysaccharide, flavonoid, and polyphenol contents ( Zhang Q. et al, 2022 ; Ziyatdinova and Kalmykova, 2023 ). Moreover, UHPLC-QE-MS identified 89 metabolites, including 20 flavonoids, 18 terpenoids, 14 phenols, 11 phenylpropanoids, 11 alkaloids, three chalcones, and four coumarin derivatives ( Supplementary Table S4 ; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…[37] Angelica and Rehmannia are capable of nourishing yin and enriching the blood, whereas Chuanxiong regulates qi and blood. [38,39] Modern research has demonstrated that THSWD possesses anti-inflammatory, analgesic, and vasodilatory properties that improve microcirculation, inhibit venous thrombosis, and enhance nonspecific immune function.…”
Section: Discussionmentioning
confidence: 99%
“…SH-SY5Y cells, a neuroblastoma cell line, have often been used as a model to study neurotoxic mechanisms [ 23 , 24 , 25 ]. Sodium para-aminosalicylic acid (PAS-Na) is a tuberculosis drug with non-specific anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%